EFEKTIFITAS MODEL PEMBELAJARAN KOOPERATIF TEAMS GAMES TOURNAMENT (TGT) PADA PEMBELAJARAN MATEMATIKA MATERI BANGUN RUANG - Suparni Suparni (IAIN PADANGSIDIMPUAN, 2016)
The background of this research is the lack of understanding in mathematics concepts and creativity Students. They have difficulty when solving geometry problems. This due by lack of learning model chosen with the material presented .the problem in this study is whether the model of cooperative learning. Teams Games Tournament (TGT) will be able to increase the understanding concept and creativity of students learning in material geometry. The purpose of this study is to describe an improved understanding of the concept and creativity in learning geometry.This research is a classroom action research, conducted on 23 students ofclass VII-A MTs.S. Pondok Pesantren Dar Al-Maarif Basilam Baru. The understanding of the concept collected using test and the creativity of student collected using observation sheets.This study was done by two cycles and each cycle consisting of two meetings. Based on test data and observation we concluded that the application of learning models Teams Games Tournament proven to improve students understanding of concept creativity in the learning of mathematics, especially geometry material.